2020
DOI: 10.1101/2020.11.11.377994
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enzyme catalysis prior to aromatic residues: reverse engineering of a dephosphoCoA kinase

Abstract: It is well-known that the large diversity of protein functions and structures is derived from the broad spectrum of physicochemical properties of the 20 canonical amino acids. According to the generally accepted hypothesis, protein evolution was continuously associated with enrichment of this alphabet, increasing stability, specificity and spectrum of catalytic functions. Aromatic amino acids are considered the latest addition to genetic code.The main objective of this study was to test whether enzymatic catal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Such a high occurrence of structure formation within the 10E library is non-intuitive and unexpected purely from its amino acid composition. However, several folders have been recently identified from the same or similar protein composition in experiments reducing extant protein compositions 15,16,18,42,43 . Where characterized in more detail, assistance of salts, metal ions or cofactor binding were found to explain the folding properties 15,18,42,44 .…”
Section: Structure Formation Is Comparable In Proteins From the Full Canonical Alphabet And Its Early Subset Unaffected By Chaperonesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a high occurrence of structure formation within the 10E library is non-intuitive and unexpected purely from its amino acid composition. However, several folders have been recently identified from the same or similar protein composition in experiments reducing extant protein compositions 15,16,18,42,43 . Where characterized in more detail, assistance of salts, metal ions or cofactor binding were found to explain the folding properties 15,18,42,44 .…”
Section: Structure Formation Is Comparable In Proteins From the Full Canonical Alphabet And Its Early Subset Unaffected By Chaperonesmentioning
confidence: 99%
“…However, several folders have been recently identified from the same or similar protein composition in experiments reducing extant protein compositions 15,16,18,42,43 . Where characterized in more detail, assistance of salts, metal ions or cofactor binding were found to explain the folding properties 15,18,42,44 . In addition, Despotovic et al recently confirmed that folded conformations of a highly acidic 60-residue protein can be induced by positively charged counterions, in case of Mg2+ corresponding roughly to its concentration in the CFPS reaction (~10mM) 45 .…”
Section: Structure Formation Is Comparable In Proteins From the Full Canonical Alphabet And Its Early Subset Unaffected By Chaperonesmentioning
confidence: 99%
See 1 more Smart Citation